Radioprotection by curcumin: A mini review: Radioprotection – Curcumin - Sruthi, P; Naidu, M M (Journal of Spices and Aromatic Crops, 2021)
Ionizing radiations are detrimental to the biological system. Exposure to ionizing radiations results in many chronic diseases including cancer. It may cause dysfunctions to almost all organs of the body depending on the total dose, duration and site of irradiation. Apart from its bad effect, radiotherapy is now extensively used for the treatment of several kinds of cancers. Still, the key disadvantage in the procedure is that normal cell, in the surrounding area of the tumor, also receiving radiation doses similar to the tumor, leads to undesirable side effects and risk to patients. Curcumin has been found to protect harmful effects of ionizing radiation. So, it can be beneficial during radiotherapy of cancer. Curcumin helps to kill tumor cells effectively by enhancing the effect of radiation. It also protects normal cells against the harmful effects of radiation. Pre clinical studies are expected to lead to clinical trials to prove the potential of this age-old golden spice for treating cancer patients. This review summarizes the protective effect of curcumin against harmful radiations.